DOES AN SME HOTEL ADOPT CUSTOMER ORIENTATION? (A Case Study in an SME Hotel in Solo, Central Java, Indonesia) - Ristiyanti Harsono Prasetijo; Sony Heru Priyanto; John Joi Ihalauw; Rooskities Andadari (STIE Pelita Nusantara Semarang, 2019)
The adoption of customer orientation by an SME hotel trying to fight for excellence in a robust competition has drawn the writer’s interest. The research question to answer is: How the SME hotel adopts the customer orientation to respond to the competition and the changing environment. The research approach is qualitative. The informants are members of the hotel management staff having hands on managerial and supervisory responsibilities. Besides interviews, the writer conducted observation and triangulation. The result of this research shows that the hotel adopts customer orientation informally. They collect, distribute and respond to the information in line with their limited knowledge and capability in a financial constraint. A unique work culture of ‘gotong royong’ is created where efforts are aimed at responding to customers’ interest, satisfaction and value The inductive process in this research enables the writer to construct a mini theory which should be proved true by quantitative researches.